AN INVESTIGATION OF STUDENT SATISFACTION FROM HOSPITALITY INTERNSHIP PROGRAMS IN GREECE - EVANGELIA MARINAKOU (Centre For Tourism Planning and Development, 2013)
The purpose of this paper was to investigate internships in the hospitality sector and identify factors that contribute to student satisfaction from this working and learning experience. Students that had completed their internships from both public and private higher education institutions in Greece participated in this study. The findings suggest that overall students demonstrated a favourable perception towards their internship experience. This research also suggests that working in a professional environment, the learning experience, social interaction with supervisors/staff and the working conditions are factors that contribute to motivation and student satisfaction from internships. Finally, student expectations towards the internship experience were focused in learning and working in a professional environment. Long working hours, low or poor pay and lack of coordination are the issues that were raised and contribute to low satisfaction.